Project management practices in engineering university. Issue 1 (September 2015) - Sirazitdinova, Y; Dulzon, A; Mueller, B
Abstract: The article presents the analysis of usage of project management methodology in Tomsk Polytechnic University, in particular the experience with the course Project management which started 15 years ago. The article presents the discussion around advantages of project management methodology for engineering education and administration of the university in general and the problems impeding extensive implementation of this methodology in teaching, research and management in the university.